Legal Protection for Trademarks That Are Substantially Similar in Business Practice in Indonesia - Azmi Fauziah Suanda; Dea Puspitasari; Mudhtia Nabila Maulud; Ikhwan Aulia Fatahillah (Journal of Human Interaction and Social Studies, 2026)
This study examines the systematic vulnerabilities embedded within the Indonesian first to file trademark registration framework under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Utilizing a qualitative normative juridical research design, the investigation evaluates the persistent misalignment between statutory mandates, administrative examinations, and judicial outcomes. The analysis shows that the absence of standardized testing metrics for the triple identity test generates severe subjectivity during the evaluation of dominant visual, phonetic, and conceptual elements. Furthermore, comparative case studies of landmark litigations expose deep inconsistencies in how commercial courts interpret bad faith intentions and cosmetic brand modifications. These institutional challenges are exacerbated by the rapid growth of the digital marketplace, which enables sophisticated lookalike storefronts to exploit existing legal voids and dilute corporate goodwill. The study concludes that building a secure and innovative domestic market ecosystem requires urgent structural reforms, including automated phonetic mapping technologies, standardized judicial evaluation guidelines, and inclusive registration pathways.